Fertility life table of the planococcus citri (risso) and planococcus minor (maskell) (hemiptera: pseudococcidae) in coffee tree - Costa, Marlice Botelho; Souza, Brigida; Prado, Ernesto; Santa-Cecília, Lenira Viana Costa (Coffee Science - ISSN 1984-3909, 2016)
The mealybugs Planococcus citri and Planococcus minor (Hemiptera: Pseudococcidae) have increased their importance in brazilian coffee and cause similar damage to plants. Our objective was to determine the characteristics related to the development of these species, testing the hypothesis that, despite of considered cryptic, they have different biological characteristics. Mealybugs crawlers were individually isolated inside Petri dishes containing coffee leaf discs on an agar layer. Its development was monitored until adult emergence when females were enclosed with a male. We evaluated fertility parameters and by means of a life table, we estimated the mean generation time (T), the reproduction net rate (Ro), the increasing net rate (Rm), the finite increasing rate (λ) and the time needed to double the number of individuals (TD). Generally, the reproductive and fertility parameters did not differ between both species. These results show that females of both species produce similar number of descendents rejecting the tested hypothesis.